Role of Gd2O3 on structure rearrangement and elastic properties ZnO-Al2O3-B2O3-SiO2 glass system - Muhammad Noorazlan Abd Azis (Tanjung Malim, 2023)
Role of Gd2O3 on structure rearrangement and elastic properties ZnO-Al2O3-B2O3-SiO2 glass system by Muhammad Noorazlan Abd Azis